STUDI KASUS PENERAPAN EVIDENCE BASED NURSING (EBN) TERAPI MUROTTAL DAN AROMATERAPI LAVENDER DALAM MENGATASI KELELAHAN PERAWAT DI RUANG HARDJA 1B RUMAH SAKIT BHAYANGKARA TK.I R. SAID SUKANTO - Asa Alamanda, (2022)
The imbalance in the workload of nurses is a problem that often arises in a hospital and often causes fatigue for nurses. The authors found data that out of 10 nurses on duty in Hardja 1B , 3 nurses were in the tired category, and 2 nurses were in very tired category, based on findings of these data, authors aimed to do work fatigue management for nurses by applying relaxation techniques namely murottal therapy and lavender aromatherapy. This case study begins by conducting pre-test using the Work Fatigue Measuring Tool Questionnaire ,after nurse fatigue data was collected, authors then carry out the implementation of nursing plan that has been made. This therapy was given for 30 minutes using a diffuser speaker which is placed ± 1 meter from intervention object, then the murottal in the form of Al-Kahf's letter chanted by Saad Al-Ghamdi played with 50 dB volume. This therapy was carried out for three consecutive days. After the therapy was completed, a post test was carried out using same questionnaire to determine the fatigue of nurses after being given therapy. The results of post test showed a decrease in the level of nurse fatigue after being given therapy